Direct-Detection OFDM Transmission Using Four-State Chirp Control With a Dual-Electrode MZM for Dispersion Compensation - Shota Ishimura; Kosuke Nishimura (IEEE Photonics Journal)
We discuss a four-state chirp-control scheme using a dual-electrode Mach–Zehnder modulator to compensate dispersion-induced RF power fading when employing direct-detection-based orthogonal-frequency-division-multiplexed (OFDM) signals. We numerically confirm that in contrast to the previously proposed parallel transmitter employing an intensity/phase modulator, four-state chirp control can flatten frequency response and make the total performance uniform even though its structure is significantly simplified. To demonstrate this, we successfully transmitted a 20-GHz OFDM signal over an 80-km single-mode fiber using four-state chirp control, achieving a line bit rate of 78.41 Gb/s even in the presence of chromatic dispersion.